Ecos da constituinte na construção de uma polícia cidadã - Mutz, Ronaldo (2008)
As part of the Military Police of the State of Espírito Santo, career started at the beninning of 1990 when I went to the Academy of Military Police of State of Minas Gerais attend the Training Course for Official, I had the opportunity to observe and act as police in the city of Belo Horizonte for a period of four years. After formed, presented me to my operational activities in the State of Espírito Santo in late 1993 and now I notice the different ways of being an act between the two corporations, in spite of performing a service that is to feature the universal quest for peace and tranquility. Over time, I had the first contact with a new method of policing, called Policing Interactive, which advocates changes in the mode of action of the police seeking the adoption of concepts aimed for citizenship and human rights initiative processed whitin the Military Police. In continuation of my operational activities, and invariably making a parallel between the forms of action police of the two corporations, several questions were accumulating if, as I intend, in this work, enter the world of another – the citizen – to pursue his version of police to provide their safety daily. A mark that was once so I could express my observation about the police, even when student – cadet -, was the reprimand commenting: “The police will begin its transformation as soon as the colonels formatted by the dictatorship put their pajamas”. My impression, to express such a comment, was that the changes democratizing processed by the new political condition of the country had not yet reached the troops, that in 1990. The reprimand was the confirmation.